The Influence of Ease of Use, Trust, and Information Quality on the Decision to Use Online Hydrological Data at the Sulawesi II River Basin Agency - Karundeng, Deby R.; Suyanto, Moh. Afan; Yakup, Yakup; Djafar, Asri (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to analyze the influence of trust, ease of use, and information quality on the decision to use online hydrological data at the Sulawesi II River Basin Agency. The sampling method was carried out through accidental sampling at the Sulawesi II River Basin Agency office in Gorontalo. Multiple linear regression analysis indicates that ease of use and trust insignificantly affect the decision to use hydrological data, while information quality has a significant positive influence. These results underscore the importance of information quality in influencing decisions regarding the use of online public services.